2013
DOI: 10.5194/bg-10-6509-2013
|View full text |Cite
|
Sign up to set email alerts
|

Air–sea exchanges of CO<sub>2</sub> in the world's coastal seas

Abstract: Abstract. The air-sea exchanges of CO 2 in the world's 165 estuaries and 87 continental shelves are evaluated. Generally and in all seasons, upper estuaries with salinities of less than two are strong sources of CO 2 (39 ± 56 mol C m −2 yr −1 , positive flux indicates that the water is losing CO 2 to the atmosphere); mid-estuaries with salinities of between 2 and 25 are moderate sources (17.5 ± 34 mol C m −2 yr −1 ) and lower estuaries with salinities of more than 25 are weak sources . Mixing with low-pCO 2 sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
275
7
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 313 publications
(318 citation statements)
references
References 245 publications
25
275
7
5
Order By: Relevance
“…This efflux compares favorably with that of the Delaware Estuary (2.4 ± 4.8 mol C m −2 yr −1 ; Joesoef et al, 2015), another large estuarine system with a long water residence time, but is significantly lower than estimates in the marinedominated Sapelo Sound and Doboy Sound estuaries (10.5 to 10.7 mol C m −2 yr −1 ; Jiang et al, 2008). From a compilation of 165 estuaries worldwide, almost all systems, with the exception of those in the Arctic (−1.1 mol C m −2 yr −1 ), serve as sources of CO 2 to the atmosphere (Chen et al, 2013). Chen et al (2013) concluded that the world's upper estuaries Table 2.…”
Section: Air-sea Co 2 Flux and Spatial Integrationmentioning
confidence: 94%
See 4 more Smart Citations
“…This efflux compares favorably with that of the Delaware Estuary (2.4 ± 4.8 mol C m −2 yr −1 ; Joesoef et al, 2015), another large estuarine system with a long water residence time, but is significantly lower than estimates in the marinedominated Sapelo Sound and Doboy Sound estuaries (10.5 to 10.7 mol C m −2 yr −1 ; Jiang et al, 2008). From a compilation of 165 estuaries worldwide, almost all systems, with the exception of those in the Arctic (−1.1 mol C m −2 yr −1 ), serve as sources of CO 2 to the atmosphere (Chen et al, 2013). Chen et al (2013) concluded that the world's upper estuaries Table 2.…”
Section: Air-sea Co 2 Flux and Spatial Integrationmentioning
confidence: 94%
“…From a compilation of 165 estuaries worldwide, almost all systems, with the exception of those in the Arctic (−1.1 mol C m −2 yr −1 ), serve as sources of CO 2 to the atmosphere (Chen et al, 2013). Chen et al (2013) concluded that the world's upper estuaries Table 2. Mean, standard deviation, and range of pCO 2 , k W-14 , k R&C-01 , F W-14 , and F R&C-01 in the surface waters of the St. Lawrence River, USLE, LSLE, and GSL during all sampling months.…”
Section: Air-sea Co 2 Flux and Spatial Integrationmentioning
confidence: 99%
See 3 more Smart Citations